The role of fairy tales in the cultivation of artistic thinking of Primary School students - Botirova Gulchehra To'lqin kizi, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
this article describes the ideological and artistic value of a fairy tale and a fairy tale, the most ancient and popular genre of Uzbek folk oral creativity, what place it occupies in the mind, imagination and upbringing of a child.